1984
DOI: 10.1161/01.res.55.6.816
|View full text |Cite
|
Sign up to set email alerts
|

Role of glycolytic products in damage to ischemic myocardium. Dissociation of adenosine triphosphate levels and recovery of function of reperfused ischemic hearts.

Abstract: SUMMARY. The mechanism of irreversible damage to ischemic myocardium was investigated in the perfused rat heart. The time of transition from reversible to irreversible damage to contractile function was accelerated by accumulation of glycolytic products and increases in extracellular calcium. Both of these effects were largely independent of adenine nucleotide levels in the tissue. With zero coronary flow and 1.25 nut calcium the decrease in ability of the heart to recover ventricular function with reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
162
3
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(185 citation statements)
references
References 23 publications
(22 reference statements)
15
162
3
3
Order By: Relevance
“…This is consistent with the observations of Ramasamy and colleagues (13)(14)(15) suggesting that inhibition of AR prevents tissue injury in ex vivo models of low-flow ischemia. The role of glycolysis during ischemia is, however, complex and although glycolysis is needed to generate ATP in the ischemic heart, accumulation of glycolytic products causes tissue injury (56). Indeed, the cardioprotective effects of early ischemic preconditioning are associated with a decrease in glycolysis (57), which may be a reflection of increased glucose utilization by activated AR.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the observations of Ramasamy and colleagues (13)(14)(15) suggesting that inhibition of AR prevents tissue injury in ex vivo models of low-flow ischemia. The role of glycolysis during ischemia is, however, complex and although glycolysis is needed to generate ATP in the ischemic heart, accumulation of glycolytic products causes tissue injury (56). Indeed, the cardioprotective effects of early ischemic preconditioning are associated with a decrease in glycolysis (57), which may be a reflection of increased glucose utilization by activated AR.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have postulated a "toxic" effect of glycogen breakdown in ischemic heart that is due to an accumulation of protons and lactate and have suggested the beneficial consequences of depleting the glycogen stores before an ischemic episode. 79 Many other studies, however, have shown that protection of the heart against ischemic injury is related to glycogen availability. 73,81,[105][106][107][108][109] The absolute amount of glucose moieties arising from glycogen is not negligible at the onset of ischemia.…”
Section: Glycogen Metabolismmentioning
confidence: 99%
“…77 In severe ischemia, myocardial glucose extraction is inversely related to coronary flow, 78 until the degree of ischemia becomes so severe that glycolysis is inhibited by the accumulation of its products. 79 Once glycolysis is inhibited, glucose uptake progressively decreases, while protons, Na ϩ , and Ca 2ϩ continue to accumulate. [80][81][82] The decline of glucose uptake during prolonged severe ischemia may be attenuated by various interventions protecting the heart against ischemic injury, such as an increase of the extracellular glucose concentration or the addition of insulin.…”
Section: Glucose Metabolism In the Ischemic And Reperfused Heartmentioning
confidence: 99%
“…Hypoxia may persist within the infarct and at its margins for days or weeks, exacerbating the injury (2)(3)(4). In response, the ischemic myocardium switches from respiration to glycolytic energy metabolism, with increased glucose consumption, lactic acid production, and lower intracellular pH (5)(6)(7). The extent of tissue loss to infarction is determined by the severity and duration of the ischemic period and is known to involve both necrotic and apoptotic cell death pathways (8)(9)(10).…”
mentioning
confidence: 99%